Aspirin and Its Potential Preventive Role in Cancer: An Umbrella Review - Song, Yongxi; Zhong, Xi; Gao, Peng; Zhou, Cen; Shi, Jinxin; Wu, Zhonghua; Guo, Zhexu; Wang, Zhenning (Frontiers in Endocrinology, 2020)
Background: Aspirin is one of the most commonly prescribed drugs worldwide and has been reported to possess anti-cancer properties in addition to antipyretic and analgesic effects. This umbrella review summarizes systematic reviews and meta-analyses that investigate the association between aspirin and cancer risk, aiming to help clinical and public health decision-makers interpret the results of these studies when re-positioning aspirin. Methods: An umbrella review of systematic reviews and meta-analyses. Results: The associations that reached statistical significance (17 in total) indicated potential preventive effects of aspirin on certain cancers or precancerous lesions. We found that no association was supported by strong evidence. Only one association (aspirin and overall cancer risk) was supported by highly suggestive evidence. The evidence supporting the association between aspirin and the risk of breast cancer, non-cardia gastric cancer, or prostate cancer was considered to be highly suggestive. The remaining 23 associations were supported by weak (13) or not suggestive evidence (10). Conclusions: The association between aspirin and a reduced risk of esophageal squamous cell carcinoma is supported by strong evidence, researchers and policy makers should pay more attention to the potential merit of repositioning aspirin to prevent esophageal squamous cell carcinoma.